EKSTRAK BIJI KESUMBA KELING (BIXA ORELLANA LINN) SEBAGAI PEWARNA ALAMI KAYU SENGON (PARASERIANTHES FALCATARIA LINN) - Putri, Ayu Rasinta; Tavita, Gusti Eva; Muflihati, . (Universitas Tanjungpura, 2016)
Kesumba keling is a potential plant as a natural dye can be obtained from the seeds containing bixin is soluble in fats and norbixin is water soluble. The purpose of this research is to find a solvent that produces the best color on staining sengon wood and find out the leaching test in cold water and hot water on sengon wood has been dyed from extract kesumba keling seed. The method used by Randomized Complete Design (RCD), which consists of five comparisons solvent. The extraction of natural dyes from kesumba keling seed using five ratio of solvent water:ethanol (1:0), water:ethanol (1:1), water:ethanol (3:1), water:ethanol (1:3) and water:ethanol (0:1) applied to sengon wood using heat soaking for 90 minutes. The leaching test is made by soaking the wood that has been stained in cold water and hot water. The next is assessed by determination of color using CIELab method. The results showed the best color sengon wood produced from wood which is stained from extraction water:ethanol (0:1), while the smallest fastness obtained from extracts of water:ethanol (1:0). The highest of level extact is produced from the seeds of the extracted water:ethanol (0:1). The result of phytochemical detect that the resulted extract containing flavonoids, terpenoids, saponins, alkaloids and steroids. Key words : Kesumba keling seed extract, natural dye, sengon